Near-Infrared Light Activated Formulation for the Spatially Controlled Release of CRISPR-Cas9 Ribonucleoprotein for Brain Gene Editing - Simões, Susana (2024)
The CRISPR/Cas9 system has emerged as a promising platform for gene editing; however, the lack of an efficient and safe delivery system to introduce it into cells continues to hinder clinical translation. Here, we report a rationally designed gene-editing nanoparticle (NP) formulation for brain applications: an sgRNA:Cas9 ribonucleoprotein complex is immobilized on the NP surface by oligonucleotides that are complementary to the sgRNA. Irradiation of the formulation with a near-infrared (NIR) laser generates heat in the NP, leading to the release of the ribonucleoprotein complex. The gene-editing potential of the formulation was demonstrated in vitro at the single-cell level. The safety and gene editing of the formulation were also demonstrated in the brains of reporter mice, specifically in the subventricular zone after intracerebral administration and in the olfactory bulb after intranasal administration. The formulation presented here offers a new strategy for the spatially controlled delivery of the CRISPR system to the brain.